Confiança na polícia em Minas Gerais: o que importa? - Geélison Ferreira da Silva (2012)
In a context of low trust in democratic institutions, factors that impact in trust in the police in Minas Gerais state are identified and analyzed. After bibliographic revision was found incipient exploration of this theme in Brazil when compared with the field, which is more developed in others countries. Trust regards beliefs and positive expectations about the institution. The concept is defined and the categorizations found about this and its relevance for the democratic regime and the police efficacy are shown. It is shown its level in the police of Minas Gerais, which is very elevated for Brazil, but very distant of the levels of countries with largest trust. The trust in the police is influenced for others institutions like government and mainly the Justice System because there is a common sense association between the functions of both institutions attributing the role of crime control to the police. Social and demographic characteristics, kind of contact between police and citizens, disorder perception in neighborhood, and perceptions of the institutionally efficiency are between the means aspects cited as able to impact the trust in police. From the research of Perception of Fear of the Violence made by CRISP in 2009 the effects this concepts and variables on the cop trust were tested empirically. More consistent results indicate that elderly and religious people tend to trust more. Socioeconomic status is negatively associated with the trust and disorder positively. Having direct contact with the police, in general, affects their trust. Newspapers and conversation with people reduces the trust. Internet and radio raise the trust, such as living in smaller cities. Realizing the polices inefficiency in the control of the violence affects negatively the trust.